Rhinosporidiosis of the tarsal conjunctiva - Nair, Akshay Gopinathan (Indian J Ophthalmol, 2015)
Rhinosporidiosis is a rare infection caused by Rhinosporidium seeberi, an organism classified in its own class, mesomycetozoea. It commonly affects mucus membranes namely the nasal mucosa, pharynx and the conjunctiva. We present the case of an 8-year-old female who presented with a flat, red, vascular, fleshy, pedunculated mass arising from the tarsal conjunctiva of the right upper eyelid. The mass was completely excised. On histopathological examination, multiple sporangia were seen in various stages of degeneration, consistent with rhinosporidiosis. The diagnosis of rhinosporidiosis is based solely on its microscopic features, and the treatment is surgical excision. This condition is endemic in the temperate regions of the Indian subcontinent, but it has been known to occur even in the colder regions of North America and Eastern Europe. Although a rare clinical entity, the possibility of rhinosporidiosis must be borne in mind when evaluating any polypoidal conjunctival mass.